Characteristic of two mouse bcr-abl-transformed cell lines: I. General properties of the cells - Sobotkova, E; Ludvíková, V; Petrácková, M; Dusková, M; Smetana, K; Jelínek, F; Marinov, I; Vonka, V (Folia biologica, 2005)
In an effort to develop an experimental system suitable for immunological studies in which Bcr-Abl-positive cells are to be used as antigens, we examined the properties of two mouse (Balb/c) established cell lines that express the Bcr-Abl protein and are oncogenic for syngeneic animals. Under standard conditions the two cell lines, viz. Ba-p210 (B210) and 12B1, expressed comparable amounts of the Bcr-Abl protein. However, they differed in a number of characteristics. From the morphological point of view, B210 cells were the more homogeneous, being mainly represented by leukaemic blastic cells with a large number of AgNORs as markers indicating a high proliferative activity. 12B1 cells were more polymorphic and giant cells were detected within their populations. Many 12B1 cells exhibited nuclear segmentation and "band-like" structures. Markers of proliferation were less frequent in 12B1 and the tendency for aging was more pronounced in these cells. The 12B1 cells were slightly more sensitive to imatinib mesylate than B210 cells. In B210 cells, the expression of MHC class I was downregulated, which was not the case with 12B1 cells. Both cell lines induced leukaemia-like disease in mice after intravenous application but, as compared with B210, 12B1 cells were about 100 times more oncogenic and the disease they induced was more aggressive. Moreover, 12B1, but not B210, induced tumours after subcutaneous or intraperitoneal inoculation.
Keywords: nádorové biomarkery; stárnutí buněk; Histocompatibility Antigens Class I; leukemie; Biomarkers, Tumor; myši inbrední BALB C; proliferace buněk; pyrimidiny; Piperazines; transformované buněčné linie; Cell Shape; Pyrimidines; Cell Line, Transformed; Cellular Senescence; Drug Resistance, Neoplasm; Down-Regulation; transplantace nádorů; tvar buňky; benzamidy; Neoplasm Transplantation; chemorezistence; zvířata; Animals; Benzamides; myši; Fusion Proteins, bcr-abl; imatinib mesylát; Cell Proliferation; Antineoplastic Agents; down regulace; Mice, Inbred BALB C; Mice; Neoplasm Invasiveness; invazivní růst nádoru; Imatinib Mesylate; nádorová transformace buněk; Leukemia; MHC antigeny I. třídy; protinádorové látky; bcr-abl fúzní proteiny; piperaziny; Cell Transformation, Neoplastic